Expression of Traditional Knowledge in Lingual Units Puger Fishermen's Community, Jember: Antropolinguistic Review - Akhmad Dzukaul Fuad; Anang Santoso; Yuni Pratiwi; Roekhan Roekhan (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This research aims to identify and describe the form of local knowledge reflected in language, which is manifested in the lingual units used in speech. Anthropolinguistics is an appropriate method for identifying the correlation between language and the cognitive and knowledge systems possessed by the Puger fishermen community. Lingual units in speech become a database as they become a means of storing, perpetuating and passing on a society's cognitive and knowledge systems. Ethnographic analysis of communication is used to obtain the socio-cultural contextuality behind the speech in the Puger fishermen community. The contextuality behind the birth of speech can provide appropriate ethnosemantic meaning in accordance with the socio-cultural perspective of the community. Ethnosemantic meaning produces a classification system that shows the ability of Puger fishermen to recognize patterns of change and determine patterns of natural phenomena that occur. This classification system is the basis for determining the form of local knowledge of the community. Based on the analysis of lingual data in speech, lingual units were obtained in the form of nouns and verbs in speech which describe the close correlation and intensity of their interaction with the sea. Local knowledge of Puger fishermen can be identified in the form of 1) knowledge about waves, 2) knowledge about water, 3) knowledge about fishing gear, and 4) knowledge about fishing techniques. Mastery of these knowledge determines accuracy and speed in making decisions to safeguard and maintain the continuity of their lives.